(untitled) - Cutnell, John D. (New York, 1995)
Presenting the concepts of physics in a clear and motivational manner, this edition of an introductory non-calculus text includes both new material and enhanced examples as well as a commonsense approach to understanding physical concepts. New topics discussed include Gauss's Law, Ampere's Law, work done by a variable force, imaging techniques (MRI, CAT and PET) and expanded reasoning steps. The book communicates technical applications and offers balanced end-of-chapter problem sets.
Keywords: Vật lý,Physics